Tunable fabry-perot optical filter with a resonant cavity based on a piezoelectric polymer - Silva, B. (2008)
This article describes a tunable Fabry-Perot optical filter with its resonant cavity based on a piezoelectric polymer, for application in the biochemical analysis of biologic fluids. The filter is composed by two thin-films of silver -mirrors- located parallel one to the other and separated by a nanometer size thin polymer film of poly(vinilidene fluoride), PVDF, in its beta- phase. When applying an electrical voltage to the mirrors, the thickness of the polymer changes, changing the distance between the mirrors and thus modifying the response of the filter. The lack of parallelism in conventional Fabry-Perot filters is solved with this approach, once the changes in polymer, reflecting variations at a molecular level, are uniform in the whole area. Therefore, this filter provides the selection of a wide range of wavelengths allowing the use of a conventional white light as source, and avoiding the use of monochromatic sources that increase substantially the price of the analysis devices and consequently the cost of the analysis.